2012
DOI: 10.3109/0886022x.2012.734938
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natrium Hyaluronate Applied Locally for Pelviureteral Anastomoses

Abstract: Objectives: This study aimed to investigate the effect of natrium hyaluronate (NH) on fibrous tissue formation and wound healing in experimental pelviureteral anastomosis (PUA). Materials and methods: Eighteen rabbits were divided equally into three groups: surgical (S), sham (Sh), and NH. A 1-cm length of the ureteropelvic segment was resected through a laparotomy incision and then anastomosis was performed. The rabbits were injected with saline (Sh group) and NH (NH group) into anastomoses lines after the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Evidence to support the role of EGF/EGF receptor signaling in the inflammatory phase of wound healing has recently been increasing . Ectogenic EGF can significantly reduce inflammation in vitro, accelerate re‐epithelialization, and increase tensile strength in wounds while regulating the correct deposition and maturation of collagen . Topical administration of EGF has been found to promote epithelialization and accelerate healing of cutaneous wounds in clinical trials …”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support the role of EGF/EGF receptor signaling in the inflammatory phase of wound healing has recently been increasing . Ectogenic EGF can significantly reduce inflammation in vitro, accelerate re‐epithelialization, and increase tensile strength in wounds while regulating the correct deposition and maturation of collagen . Topical administration of EGF has been found to promote epithelialization and accelerate healing of cutaneous wounds in clinical trials …”
Section: Discussionmentioning
confidence: 99%
“…Also, increased phosphorylation of EGFR resulted in an upsurge of MAP-ERK-1 and ERK-2 kinase phosphorylation levels and actions with more than 440% and 880% folds, respectively, at the initial phases of the healing of an experimental gastric ulcer accelerated healing [43]. An increased EGFR expression indicates a vital role of EGF in ulcer healing and scar formation [41,44]. e development of granulation tissue at ulcer base, new blood vessels formation otherwise called angiogenesis, and restitution of the full glandular architecture of the damaged mucosa may take a few weeks [45].…”
Section: Discussionmentioning
confidence: 99%
“…Hellstrom et al 10 showed that hyaluronan-treated perforations closed more rapidly than did untreated perforations in a model of induced tympanic membrane perforations in rats. Yurtçu et al 11 reported that hyaluronan facilitated wound healing by increasing re-epithelialization and neovascularization in an experimental model of pelviureteral anastomosis in rabbits. Lan et al 13 reported that hyaluronan suppressed colonization, growth, and metastasis of a gastric cancer cell line in an experimental model.…”
Section: ■ Discussionmentioning
confidence: 99%
“…application, including in patients with skin damage, chronic venous leg ulcers, tympanic membrane perforation, and pelviureteral anastomoses [8][9][10][11] . Hyaluronan is used to prevent postoperative adhesions because it creates a physiological barrier between the healing tissue and other tissue surfaces during peritoneal reepithelialization 12 .…”
mentioning
confidence: 99%